(untitled) (Research, Society and Development, 2020)
Urban development and disordered population growth have caused several negative impacts on natural resources, especially water resources, particularly in terms of water quality and the way they are being managed. This work aims to carry out a study on water characterization, with emphasis on the physical, chemical and biological characteristics of the waters of the Avenida Visconde de Souza Franco channel in the city of Belém-Pará. The analyzed parameters were established in accordance with resolution No. 357/2005 of the National Environment Council (CONAMA), which provides for the classification of bodies of water and the environmental guidelines for their classification, as well as establishing the conditions and standards effluent discharge. In this study, in addition to the parameters of Resolution No. 357/2005, the requirements established by the Environmental Sanitation Technology Company (CETESB) for checking the conductivity in the water body, for the characterization of the waters of the Doca channel, were considered flow into Guajará Bay, Belém-PA. From the analysis of the quality parameters of the water body, it was possible to verify deviations from standards in the physical-chemical and bacteriological characteristics of the Av. Visconde de Souza Franco channel, identifying the irregular discharge of domestic and industrial sewers.